Глава 3.10. Усиновлення у найкращих інтересах дитини: судовий розгляд справ та виконання рішень (на прикладі України та Швейцарії) - Бордюг, Тетяна Олександрівна (Цивільний та виконавчий процес: міжгалузеві зв’язки. Особливості розгляду судами певних категорій справ та виконання судових рішень. Монографія, 2024)
This research paper examines the principle of the best interests of the child in the context of adoption, comparing approaches and practices in Ukraine and Switzerland. The author analyzes the interpretation of the best interests of the child, considering various definitions and approaches to assessing the best interests of the child in the doctrine and legislation of both countries, as well as the legislative framework and adoption procedure, including requirements for adopters, the adoption process, and the specifics of international adoption.The paper also analyzes in detail examples of court decisions from both countries concerning the adoption of a child from among relatives; cancellation of adoption; recognition of a foreign adoption decision; parental consent for adoption; adoption by a stepfather; absence of consent of one of the parents.The author also examines the mechanisms and specifics of the enforcement of court decisions in adoption cases in both countries.The conclusions made in the chapter include, in particular, the fact that Ukraine and Switzerland recognize the fundamental principle of the best interests of the child in adoption cases. There are certain differences in the interpretation and application of this principle: in Ukraine, the emphasis is on providing the child with a stable and safe environment, emotional connection with adopters, and the opportunity for development and realization of their potential, while the Swiss practice is more flexible, also taking into account the child’s cultural identity and the possibility of maintaining ties with the biological family.The legislation and adoption procedures in Ukraine and Switzerland have common features regarding requirements for adopters (age, marital status, income, health status); adoption process (collection of documents, assessment of candidates, interviews, court decision); specifics of international adoption (additional procedures, control over the observance of children’s rights). There are also significant differences: in Ukraine, adoption is possible only by a court decision, while in Switzerland, notarization through authorized state bodies is also allowed; in Ukraine, there are stricter requirements for the age of adopters and the age difference with the child.The court practice in adoption cases demonstrates similar approaches to resolving certain categories of cases concerning the adoption of a child from among relatives (taking into account motives, emotional connection, and the possibility of ensuring the best interests of the child); cancellation of adoption (possible only in exceptional circumstances that significantly harm the best interests of the child); recognition of a foreign adoption decision (carried out taking into account international treaties and principles).